2018
DOI: 10.7575/aiac.ijalel.v.7n.5p.117
|View full text |Cite
|
Sign up to set email alerts
|

President Joko Widodo’s Rhetorical Technique of Arguing in the Presidential Speeches of the Reform Era

Abstract: A good speech has the power in presenting the rhetorical argument, therefore it is required a study corresponds to the speech preparation with rhetorical techniques to argue, especially in the presidential speech of the President of the Republic of Indonesia Joko Widodo of reform era in the field of education. The research method was the critical discourse analysis method of Norman Fairclough model. Data collection techniques used were documentation techniques, note-taking techniques, and interviews. Data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Likewise, presidential speeches contain substantial amount of information (Banguis-Bantawig, 2019;Eshbaugh-Soha, 2010b) and are far more influential than any other speeches made by an individual (Eriyanto, 2000;Eshbaugh-Soha, 2008;Eshbaugh-Soha, 2010a;Grice, 2010;Perloff, 1998) as they can sway people to take action, (Eshbaugh-Soha, 2010a;Rezaei & Nourali, 2016) and are likely to represent different events and developments in a country from different timelines and scopes (Chinwendu Israel & Botchwey, 2017;Mazlum & Afshin, 2016;Shaw, 2017). Rubic-Remorosa (2018) and McDougal (2013) revealed that perennial problems of a country could be seen through the speeches of the president as well as how such speeches are used to convey the possible solutions to these problems (Noermanzah et al, 2018). On the same note, Eshbaugh-Soha (Eshbaugh-Soha, 2010b) and Shaw (2017) suggested that presidential speeches are vital to governance and could only be effective when expressed publicly (Eshbaugh-Soha, 2008) in which the president could manifest desired intentions, policies, and capabilities (Sharififar & Rahimi, 2015)as well as what were achieved during the presidency are manifested (Shayegh & Nabifar, 2012).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Likewise, presidential speeches contain substantial amount of information (Banguis-Bantawig, 2019;Eshbaugh-Soha, 2010b) and are far more influential than any other speeches made by an individual (Eriyanto, 2000;Eshbaugh-Soha, 2008;Eshbaugh-Soha, 2010a;Grice, 2010;Perloff, 1998) as they can sway people to take action, (Eshbaugh-Soha, 2010a;Rezaei & Nourali, 2016) and are likely to represent different events and developments in a country from different timelines and scopes (Chinwendu Israel & Botchwey, 2017;Mazlum & Afshin, 2016;Shaw, 2017). Rubic-Remorosa (2018) and McDougal (2013) revealed that perennial problems of a country could be seen through the speeches of the president as well as how such speeches are used to convey the possible solutions to these problems (Noermanzah et al, 2018). On the same note, Eshbaugh-Soha (Eshbaugh-Soha, 2010b) and Shaw (2017) suggested that presidential speeches are vital to governance and could only be effective when expressed publicly (Eshbaugh-Soha, 2008) in which the president could manifest desired intentions, policies, and capabilities (Sharififar & Rahimi, 2015)as well as what were achieved during the presidency are manifested (Shayegh & Nabifar, 2012).…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Pada kalimat kedua penulis meneruskan wacana penulisan dengan menulis pembenaran berupa data atau fakta untuk mendukung pernyataan sebelumnya, paragraf di atas hanya terdiri dari dua kalimat tanpa diikuti kesimpulan yang logis dari pernyataan dan pembenaran yang ada sangat jelas memiliki perbedaan pola dengan paragraf yang lainya. Ciri-ciri paragraf argumentasi terdiri dari tiga bagian yang paling penting, yaitu mengandung kebenaran untuk mengubah sikap dan keyakinan orang mengenai sebuah topik yang dibahas berupa atau pernyataan mengandung data atau fakta-fakta yang berupa pembenaran yang dapat dipertanggung jawabkan, serta penjelasan yang disampaikan melalui paragraf argumentasi secara logis untuk suatu kesimpulan (Noermanzah, 2018;Keraf, 2010). Terlihat jelas pernyataan yang dikemukakan diikuti dengan pembenaran, pola ini sangat sederhana secara kualitas isi maupun makna.…”
Section: Pembahasanunclassified
“…Speech is a power in itself, it means that through speech, the speakers can persuade the listeners (Noermanzah et al, 2018). More & Carling (1982) as cited in Purba (2015:75) state that, an interlocutor must be able to revise the sound uttered by another to locate some appropriate area within his store of accumulated and generalized experience.…”
Section: A Introductionmentioning
confidence: 99%